Coverage of hospital nursing absenteeism in the composition of the Technical Safety Index: is 6.67% sufficient? - Jéssica Azevedo Guardalupe; Nicole Hertzog Rodrigues; Yasmin Lorenz da Rosa; Handyer Alakies Borges de Borba; Juliana Petri Tavares; João Lucas Campos de Oliveira (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To map scientific evidence on the (in)adequacy of the Technical Safety Index provided by the Federal Nursing Council to cover absenteeism rates in Brazilian hospital nursing. Method: Scoping review conducted according to Joanna Briggs Institute criteria. The search was carried out in February 2024, in the sources: Virtual Health Library, Scientific Electronic Library Online, Web of Science, Scopus, MEDLINE, CAPES Periodical Portal and Brazilian Digital Library of Theses and Dissertations. Cross-sectional studies conducted in the hospital environment, published between 2004 and 2024, were included. After selecting the recruited material (n=1,297), the sample (n=29) was analyzed using descriptive statistics. Results: Of the selected studies, 86.2% indicated superiority in the percentage of absence coverage recommended by the entity. Absenteeism rates ranged from 0% to 44.7% among nurses and from 0.47% to 46% among technicians/assistants. The estimated technical safety index ranged from 8.3% to 53% for nurses and from 8.77% to 54.3% for mid-level professionals. Final considerations: There is evidence to support that the minimum percentage of absenteeism coverage (6.7%) provided for by the regulatory entity is not sufficient, especially in the context of public hospitals.